2018
DOI: 10.1080/09537287.2018.1433887
|View full text |Cite
|
Sign up to set email alerts
|

A model of continuous improvement programme management

Abstract: The aim of this study is to identify key management decisions that enable the sustainment of a continuous improvement (CI) initiative. To accomplish this aim, we examine the procedures and practices used by two manufacturing companies for the management of their CI initiatives; one that is successfully sustaining the effectiveness of its CI initiative and another failing to do the same. This research makes two contributions to the conceptual understanding of CI programme management. First, we identify five CI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 39 publications
0
28
0
3
Order By: Relevance
“…Refers to evolving processes to explore superior approaches during the process of transforming inputs into outputs in an endless improvement loop [68]. It is an on-going effort to refine inter-linked processes in the light of their efficiency and flexibility [69].…”
Section: Continuous Improvementmentioning
confidence: 99%
“…Refers to evolving processes to explore superior approaches during the process of transforming inputs into outputs in an endless improvement loop [68]. It is an on-going effort to refine inter-linked processes in the light of their efficiency and flexibility [69].…”
Section: Continuous Improvementmentioning
confidence: 99%
“…PC 1 explained 97.91% of total variation from original CTQs and was the only principal component scores evaluated. These scores were adjusted by using analysis of variance, according to the model in (2). Table 4 presents the square root of variance component for this multivariate GR&R study.…”
Section: B Measure Phase 1) Select Ctqs and Validate Measurement Systemmentioning
confidence: 99%
“…It is essential to highlight that the most variation in PC 1 is due to the feed rate factor. In order to find the best fit for this turning process, several models were analyzed, taking account of lack-of-fit test, Anderson-Darling normality test for residuals and adjusted coefficient of determination (R 2 Adj ). Non-significant impact on PC 1 was provided by the cutting speed factor.…”
Section: Analyze Phasementioning
confidence: 99%
“…Previous studies have identified many factors that implementation of CI or Kaizen. Among the important components for the CI process are management commitment, customer focus, training, communication process, organizational culture, documentation, and evaluation [43,44]. A systematic literature study carried-out by Carnerud et al…”
Section: B Continuous Improvement and Quality Conceptmentioning
confidence: 99%
“…D. User Quality (USQ) -The tendency and effectiveness of end-users to use the IS solutions affected by various attributes [19,39,40,41]. E. Continuous Improvement (CQI) -Based on the Kaizen concept, to measure the application of CI upon implementing and deploying IS solutions at workplace [13,14,43,44]. F. User Satisfaction (USS) -The degree of how well the expectation and satisfaction of end-users when using IS solutions [5,7,19,36,37] and organization when it is implemented and use within the university [5,6,7,26,42].…”
Section: Details Definition Of Each Construct/dimension Are As Follow;mentioning
confidence: 99%